Education in society : readings - Meltzer, Bernard N.; Doby, Harry R. ;Smith, Philip M. ([Place of publication not identifed] : [publisher not identified], 1958)
The task we have assumed in this book of readings is to make available the contributions of the science of sociology to an understanding of education as a social process. We have used sociological concepts and principles as an implicit directive for pointing up those problems we consider crucial in the sphere of education today. No attempt has been made to avoid controversial problems. On the contrary, we have found in current controversy the clearest statement of many of the issues confronting education today. By a careful selection of readings and the inclusion of opposing points of view on controversial issues, we have attempted to avoid bias and to maintain a high level of objectivity so that our book might be of value regardless of what "side" the reader may take in any particular controversy.
Part 1. The Field of educational sociology -- Part 2. Culture and the school - Part 3. Cultural change and problems of education -- Part 4. The Social functions of education -- Part 5. The Social control of education -- Part 6. The School and the community -- Part 7. The Teacher as a person -- Part 8. The Student as a person -- Part 9. Social factors in the learning process -- Part 10. Controversial issues in education.
Includes bibliographical references.
Keywords: EDUCATION -- SOCIETY